2018
DOI: 10.1002/jia2.25201
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with liver fibrosis and steatosis by transient elastography in patients with HIV mono‐infection under long‐term combined antiretroviral therapy

Abstract: IntroductionNon‐alcoholic fatty liver disease is characterized by the presence of hepatic steatosis and can be associated with fibrosis progression, development of cirrhosis and liver‐related complications. Data on the prevalence of liver fibrosis and steatosis in HIV patients remain contradictory in resource‐limited settings. We aimed to describe the prevalence and factors associated with liver fibrosis and steatosis in patients with HIV mono‐infection under long‐term antiretroviral therapy (ART) in Rio de Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 41 publications
5
49
0
Order By: Relevance
“…In our cohort, we can confirm a high prevalence of severe hepatic steatosis of 41% in HIV patients compared to the general population, where NAFLD affects 25% of the population . This is in line with many previous studies and underlines the robustness of our data …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cohort, we can confirm a high prevalence of severe hepatic steatosis of 41% in HIV patients compared to the general population, where NAFLD affects 25% of the population . This is in line with many previous studies and underlines the robustness of our data …”
Section: Discussionsupporting
confidence: 92%
“…Importantly, risk factors for hepatic steatosis are similar in HIV‐infected patients and general population, namely obesity, dyslipidaemia and features of metabolic syndrome . However, co‐infection with certain genotypes of HCV are reported to cause hepatic steatosis .…”
Section: Discussionmentioning
confidence: 99%
“…From the results of our study, the independent predictors of NAFLD were high BMI, advance age, and serum TG level higher than 150 mg/dL which are similar to the results from the previous studies [12,[14][15][16]28]. Screening for the presence of NAFLD in HIV patients who have these factors is useful for early detection of NAFLD in these patients.…”
Section: Discussionsupporting
confidence: 89%
“…A recent metaanalysis study of 10 moderate to low quality articles using different methods to assess hepatic steatosis demonstrated that the prevalence of NAFLD was 35% (95%CI, 29-42) [14]. CAP at least 248 dB/m was used to define NAFLD in this study, similarly to the previous studies [15,20]. However, using various cutoffs values for NAFLD may lead to a wide range of prevalence of NAFLD in HIVinfected population [16,28,30].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation